Micro Approaches to Foreign Exchange Determination - Martin D. D. Evans; Dagfinn Rime (Norges Bank, 2011)
Micro-based exchange-rate research examines the determination and behavior of spot exchange rates in an environment that replicates the key features of trading in the foreign exchange (FX) market. Traditional macro exchange-rate models play little attention to how trading in the FX market actually takes place. The implicit assumption is that the details of trading are unimportant for the behavior of exchange rates over months, quarters or longer. Micro-based models, by contrast, examine how information relevant to the pricing of FX becomes reflected in the spot exchange rate via the trading process. According to this view, trading is not an ancillary market activity that can be ignored when considering exchange-rate behavior. Rather, trading is an integral part of the process through which spot rates are determined and evolve. The past decade of micro-based research has uncovered a robust and strong empirical relation between exchange rates and measures of FX trading activity. One measure in particular, order flow (i.e., the net of buyer- and seller-initiated FX trades) appears as the proximate driver of exchange-rate changes over horizons ranging from a few minutes to a few months. This finding supports the view that trading is an integral part of exchange-rate determination. It also stands in stark contrast to the well-known deficiencies of macro models in accounting for exchange-rate variations over horizons shorter than a couple of years. In this paper we provide an overview of micro-based research on exchange-rate determination. We survey both models focusing on partial equilibrium, the traditional domain of microstructure research, and recent research that focuses on the link between currency trading and macroeconomic conditions in the general equilibrium setting of modern macroeconomic models. We believe micro-based research is making some progress towards understanding the links between macroeconomic conditions and the behavior of exchange rates over macro- and policy-relevant horizons.
hdl:11250/2496957
Keywords: F3; F4; G1; 330; exchange rate dynamics; microstructure; order flow